The impact of sarcopenia on prognosis and fruquintinib efficacy in advanced colorectal cancer: a retrospective and mendelian randomization study - Wang, Yao; Meilu, Du; Qi, Shi; Yufei, Tang; Song, Gao; Susu, Han; Haotian, Wen; Tingting, Zhu; Chao, Wang; Fenggang, Hou; Xiaoling, Yin (Frontiers in Immunology, 2025)
BackgroundReportedly, sarcopenia is associated with prognosis in advanced colorectal cancer (CRC) patients and can lead to reduced efficacy of targeted therapy. However, studies on the relationship between sarcopenia and the prognosis (or efficacy) of advanced CRC patients receiving fruquintinib targeted therapy remains scarce. Therefore, we conducted a comprehensive assessment of the relationship between nutritional status, inflammation, immune function, and cancer-related sarcopenia. We also investigated whether sarcopenia affects the therapeutic efficacy of fruquintinib targeted therapy.Patients and methodsIn this retrospective study, sarcopenia and several markers of nutritional status and immune function were assessed in advanced CRC patients with fruquintinib therapy at the hospital. We used drug target mendelian randomization (MR) analysis to investigate the impact of fruquintinib on sarcopenia.ResultsAdvanced CRC patients with sarcopenia had a poorer prognosis compared to those without sarcopenia. Furthermore, sarcopenia showed a strong correlation with various markers of nutritional status, immune function indicators, inflammation markers, quality of life scores, and the prognostic nutrition index. MR studies suggest that the spleen tyrosine kinase (SYK) gene is a key factor in the occurrence of sarcopenia associated with the use of fruquintinib.ConclusionSarcopenia could be a prognostic factor in patients with advanced CRC receiving fruquintinib targeted therapy.